K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

5 tháng 10 2016

a) \(x^2-3x+xy-3y=\left(x^2-3x\right)+\left(xy-3y\right)\)

\(=x\left(x-3\right)+y\left(x-3\right)=\left(x+y\right)\left(x-3\right)\)

b) \(x^3-2x^2+x=x\left(x^2-2x+1\right)=x\left(x-1\right)^2\)

c)\(x^3+2x^2y+xy^2-9x=x\left(x^2+2xy+y^2-9\right)\)

\(=x\left[\left(x+y\right)^2-3^2\right]=x\left(x+y-3\right)\left(x+y+3\right)\)

5 tháng 10 2016

Câu a là x mũ 2. Còn câu b là x mũ 3 nha m.n

1: \(=x^2+6x+9-y^2\)

\(=\left(x+3\right)^2-y^2\)

\(=\left(x+3+y\right)\left(x+3-y\right)\)

2: \(x^2-2xy+y^2-25\)

\(=\left(x-y\right)^2-25\)

\(=\left(x-5-y\right)\left(x+5-y\right)\)

4: \(=y\left(x-y\right)-5\left(x-y\right)=\left(x-y\right)\left(y-5\right)\)

5: \(=x^3\left(x+3\right)-9\left(x+3\right)\)

\(=\left(x+3\right)\left(x^3-9\right)\)

18 tháng 7 2019

a) 6x^2+27x+4x+18-[ 6x^2+x+12x+2]=7

6x^2+31x+18-6x^2-13x-2=7

18x+16=7

18x=-9

x=-1/2

18 tháng 7 2019

(6x-3)(3x-1)-[18x^2-2x-27x+3]=0

18x^2-6x-9x+3-18x^2+2x+27x-3=0

14x=0

x=0

10 tháng 9 2018

1/

a. \(3x\left(5x^2-2x-1\right)\)

\(=15x^3-6x^2-3x\)

b. \(\left(x^2-2xy+3\right)\left(-xy\right)\)

\(=-x^3y+2x^2y^2-3xy\)

c. \(\left(2x^2-3xy+y^2\right)\left(x+y\right)\)

\(=2x^3-3x^2y+xy^2+2x^2y-3xy^2+y^3\)

\(=2x^3-x^2y-2xy^2\)

10 tháng 9 2018

a) thiếu đề

b) \(\left(3x-3\right)\left(5-21x\right)+\left(7x+4\right)\left(9x-5\right)=44\)

\(15x-63x^2-15+63x+63x^2-35x+36x-20=44\)

\(79x-35=40\)

\(79x=75\)

\(x=\frac{75}{79}\)

14 tháng 8 2015

a/ \(=3y^2-6y-2x+1\)

b/ \(=-\left(x^3-3x^2+3x-1\right)=-\left(x-1\right)^3\)

c/ \(=\left(2-x\right)^3\)

d/ \(=xy^2+x^2y+3xy+x^2y+x^3+3x^2-3xy-3x^2-9x\)

\(=xy\left(y+x+3\right)+x^2\left(y+x+3\right)-3x\left(y+x+3\right)\)

\(=\left(xy+x^2-3x\right)\left(y+x+3\right)=x\left(y+x-3\right)\left(y+x+3\right)\)

e/ \(=xy-x^2+2x-y^2+xy-2y\)

\(=x\left(y-x+2\right)-y\left(y-x+2\right)=\left(x-y\right)\left(y-x+2\right)\)

14 tháng 8 2015

a) =(2x+3y-1)2

b)=-(x-1)3

c)=-(x3-6x2+12x-8)=-(x-2)3

d)x3 + 2x2y + xy2 – 9x

    = x(x2 + 2xy + y2 -9)

    = x[(x2 + 2xy + y2) - 32]

    = x[(x + y)2 - 32]

    = x (x + y – 3)(x + y + 3)

e) 2x-2y-x2+2xy-y2=2(x-y)-(x-y)2=(x-y)(2-x+y)